Estresse por Al: alterações ecofisiológicas e bioquímicas em variedades do maracujazeiro - Araujo, Raquel Alves (2012)
The toxicity of aluminum (Al) is a limiting factor on growth and development of most crops. The objective of this study was to evaluate the effect of Al on physiological aspects of the passion fruit cv. Maguary (FB 100) and cv. Yellow Master (FB 200) of seedlings, in the greenhouse, grown in the field. Were analyzed aspects of gas exchange, chlorophyll fluorescence, chlorophyll content and specific activity of SOD, catalase and ascorbate peroxidase, in plants, in two different situations. Measurements in the greenhouse were conducted on plants grown for 45 days in plastic pots containing washed sand and irrigated with nutrient solution containing 0 mM Al (pH 6), 0, 0.2 and 2.0 mM Al (pH 4) for 10 days. The measurements in field were performed in three crops of one year old containing 0 (pH 6), 0.33 (pH 5.6) and Al 2.6 mM (pH 4.7). In young plants, there was only declining trends in net assimilation of CO2 that have not materialized in significant events. There were also no major changes in antioxidant enzyme activity. Nevertheless, the cultivars FB 100 and FB 200 exhibit differential responses to exposure to Al solution. However, the pattern shown by K and L bands over the days of treatment show that the presence of Al in solution is a stressor only up to five days of treatment in the cultivar FB 100 and only 10 days to grow in the FB 200. In plants exposed to Al in natural conditions there were also no significant changes in gas exchange. But the activity of SOD and ascorbate peroxidase were higher only in plants exposed to higher concentration of Al in plants exposed to lower concentrations, there was the presence of K and L bands negative, indicating that plants were under stress. The results indicate that Al is not capable of causing great damage to the photosynthetic apparatus of passion